Analisis Penipuan Transaksi Tiket Konser Secara Online : Studi Kasus Penjualan Tiket Golden DiscAward 2024 di Media Sosial Twitter - Sefika Pradana (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
The growth of digital transactions has made it easier for people to buy goods or services, including concert tickets. However, this convenience also increases the risk of fraud, especially through social media. The case of Golden Disc Award (GDA) 2024 ticket fraud on Twitter shows a systematic modus operandi, such as the use of fake accounts and identities, suspiciously cheap ticket prices, and the transfer of communication to private platforms. Victims suffer material and psychological losses, while perpetrators often disappear after receiving payment. Legally, these actions violate Article 378 of the Criminal Code, the Electronic Information and Transactions Law, and consumer rights as stipulated in the Consumer Protection Law (UUPK). This study emphasizes the importance of consumer protection in digital transactions, strengthening regulations, and improving public digital literacy to prevent fraudulent practices. Collaboration between the government, law enforcement agencies, concert organizers, digital platforms, and consumers is key to improving the security of online transactions.